Do the Insurance Companies Lose Trust in Bangladesh? Empirical Evidence from the Customer & Managerial Perspectives. - Biswas, Tanmay (Universitas Kuningan, 2024)
This study aims to ascertain the factors influencing customer satisfaction and trust in insurance companies in Bangladesh, while also identifying the underlying reasons for the erosion of customer trust in insurance services from a managerial perspective. The research adopted an empirical survey design, incorporating a questionnaire that featured an interview component, with participation from 250 individuals. The analysis of partial least squares structural equation modeling (PLS-SEM) was conducted utilizing Smart-PLS 4.0 software, which facilitated the assessment of frequency, reliability, validity, and hypothesis testing. In the customer survey, an empirical and descriptive method was employed from a managerial perspective. A positive correlation was observed between the SERVQUAL characteristics of tangibility, responsiveness, empathy, and assurance of service quality, alongside the satisfaction and trust exhibited by customers. The findings of the study indicate that the relationships between Assurance and overall customer satisfaction (t=4.463, β=.072, p<0.05), Empathy and overall customer satisfaction (t=2.167, β=0.067, p<0.05), responsiveness and overall customer satisfaction (t=2.512, β=.069, p<0.05), tangible and overall customer satisfaction (t=4.299, β=0.058, p>0.05), as well as the relationship between overall customer satisfaction and Trust (t=18.258, β=0.04, p>0.05) exhibit statistical significance. Furthermore, the association between reliability and overall customer satisfaction (t=1.066, β=0.079, p>0.05) is statistically significant. Additional evidence indicating customer dissatisfaction with products exhibiting varying levels of dependability is the observed negative correlation between dependability and satisfaction. The findings of this study indicate that the reliability of insurance plans does not influence the level of satisfaction that customers perceive they have attained. Upon comparison with the acceptance criterion of 1.96, the T statistic for the reliability hypothesis H2 is determined to be 1.066, which is below the specified value. The P value of 0.286 exhibits a considerable divergence from the established threshold of significance, which is set at 0.05. Both of these numbers fall below the requisite conditions necessary for acceptance. The primary limitation of the study pertains to the restricted geographical scope of the research conducted. The research presents numerous implications for researchers, insurance providers, leadership groups, customer service representatives, stakeholders, and customers in identifying and assessing the factors that influence the quality of insurance services. This understanding is essential for the formulation of strategies and policies aimed at enhancing insurance services.